Ritter Reaction on Terpenoids, I Stereospecific Preparation of (1S,5R,8R) and (1R,5S,8S) 8-Acetamido-2,4,4,8-tetramethyl-3-aza-bicyclo[3.3.1]non-2-ene Perchlorate - Caram, José Alberto (1984)
Treament of ( + )lim onene with diluted perchloric acid in acetonitrile solution afforded (1S, 5R, 8R) 8-acetam ido-2,4,4.8-tetram ethyl-3-aza-bicyclo[3.3.1]non-2-ene perchlorate while the same reaction on ( — )β-pinene produced the (1S, 5R, 8R) enantiom er, and terpinolene gave the racemic mixture. The structure o f the product is proposed on basis of its physical and spectroscopic (IR , ¹H and ¹³C NMR, MS) properties and its formation involves a Ritter reaction between the monoterpene and acetonitrile.